Perceptions of the International Baccalaureate (IB) in Ontario Universities - Fitzgerald, Saira (Canadian Journal of Education/Revue canadienne de l'éducation, 2015)
This article presents the results of the first phase of a research project on perceptions of the International Baccalaureate Diploma Program (IBDP) in Canadian universities. Establishing explicit university recognition policies for IBDP students has been an ongoing task for the International Baccalaureate Organization (IBO), which conducted two studies on university perceptions of the IBDP in the UK (2003) and Australia/New Zealand (2007). The present study replicates these studies in the Canadian context, to discover how admissions officers in Ontario universities perceive the IBDP in relation to other curricula. Preliminary results reveal a high degree of uniformity in responses, consistent with the previous studies. The IBO is indicated as being the primary source of information, suggesting that it plays an important part in forming perceptions of the IBDP.